Crosscurrents in Adventist Christology - Webster, Eric C. (American university studies / 7, 1984)
For those wanting to understand Adventist christology, this book dissects the christologies of Ellen G White and E J Waggoner of the 19th century, and Edward Heppenstall and Herbert Douglass of the 20th century. - Introduction, 1. Historical Perspective and Adventist Orientation, 2. The Christology of Ellen Gould White, 3. The Christology of Ellet Joseph Waggoner, 4. The Christology of Edward Heppenstall, 5. The Christology of Herbert Douglass, 6. In Summary and in Reflection, Bibliography, Appendix to Chapter Two